Exploration of system modeling and simulation methods. (November 2020) - Meng, Lin; Gu, Ping; Yue, Xiaodong; Li, Siyu; He, Jian
Abstract: With the rapid development of science and technology, simulation has become an indispensable means to study the laws of objective things. This paper introduces the concept, method and challenge of system simulation. The key of modeling in system simulation is put forward. Finally, the common modeling methods of information systems are introduced, and the advantages and disadvantages of different modeling methods and applications are compared and analyzed.